2013
DOI: 10.1093/ejcts/ezs711
|View full text |Cite
|
Sign up to set email alerts
|

The effects of lung resection on physiological motor activity of the oesophagus†

Abstract: OBJECTIVES:To assess the modifications of oesophageal function after major lung resection and whether these modifications are correlated with the extent of resection ( pneumonectomy vs others). METHODS:In the last 5 years, 40 consecutive surgical patients with lung cancer were prospectively enrolled and divided in two groups: Group A (n = 20) patients scheduled for elective pneumonectomy and Group B (n = 20) for more limited resections (lobectomy or bilobectomy). In addition to routine evaluations, all patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Basseri et al observed a 6-fold increased risk for esophageal peristaltic dysfunction in lung transplant patients compared with healthy subjects (19). This is in line with data provided by Fiorelli and co-workers, who confirmed that pneumonectomy may cause significant EMD with reduction in LES resting pressure, especially when compared to lesser resections (20). Interestingly this did not The results are given as median including the range.…”
Section: Discussionsupporting
confidence: 70%
“…Basseri et al observed a 6-fold increased risk for esophageal peristaltic dysfunction in lung transplant patients compared with healthy subjects (19). This is in line with data provided by Fiorelli and co-workers, who confirmed that pneumonectomy may cause significant EMD with reduction in LES resting pressure, especially when compared to lesser resections (20). Interestingly this did not The results are given as median including the range.…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, only the superior segment prevented a rapid mediastinal shift and did not cause serious complications, such as postpneumonectomy syndrome or dysphagia. 7) This unique technique that avoids pneumonectomy is quite useful for preserving the patient's long-term quality of life after surgery.…”
Section: Commentmentioning
confidence: 99%
“…However, if poorly prepared, the presence of gastric mucosa above a fundoplication may result in continued acid exposure with resultant symptoms of reflux. Previous studies have shown that thoracic and abdominal surgeries can alter esophageal motility and physiology which can lead to adverse post-surgical outcomes [7,8]. Recent studies on objective changes in esophageal motility and acid exposure after Collis gastroplasty in patients undergoing PEH repair is lacking.…”
Section: Introductionmentioning
confidence: 99%